2015
DOI: 10.1242/jeb.124958
|View full text |Cite
|
Sign up to set email alerts
|

Tail loss and narrow surfaces decrease locomotor stability in the arboreal green anole lizard (Anolis carolinensis)

Abstract: Tails play an important role in dynamic stabilization during falling and jumping in lizards. Yet tail autotomy (the voluntary loss of an appendage) is a common mechanism used for predator evasion in these animals. How tail autotomy has an impact on locomotor performance and stability remains poorly understood. The goal of this study was to determine how tail loss affects running kinematics and performance in the arboreal green anole lizard, Anolis carolinensis. Lizards were run along four surface widths (9.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 80 publications
(104 reference statements)
2
26
0
Order By: Relevance
“…Though faster speeds may facilitate dynamic stability, particularly in the rolling plane (Bruijn et al, 2009), fast travel also reduces agility (Hyams et al, 2012;Wheatley et al, 2015;Wynn et al, 2015) and increases peak force production (Weyand et al, 2000) -both of which may compromise stability when moving on a precariously narrow support. Indeed, substrate narrowness has previously been shown to be associated with slower travel speeds in many arboreal tetrapods, including tree frogs (Herrel et al, 2013), anoles (Losos and Sinervo, 1989; Losos and Irschick, 1996; Mattingly and Jayne, 2004;Hsieh, 2016), fence lizards (Sinervo and Losos, 1991), marsupial gliders (Karantanis et al, 2015), opossums (Lammers and Biknevicius, 2004;Shapiro et al, 2014), mice (Hyams et al, 2012), squirrels (Schmidt, 2011) and strepsirrhine primates (Stevens, 2007). Other gait adjustments were subtler, often displaying a complex interaction with speed.…”
Section: Influence Of Support Diameter On Gait Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though faster speeds may facilitate dynamic stability, particularly in the rolling plane (Bruijn et al, 2009), fast travel also reduces agility (Hyams et al, 2012;Wheatley et al, 2015;Wynn et al, 2015) and increases peak force production (Weyand et al, 2000) -both of which may compromise stability when moving on a precariously narrow support. Indeed, substrate narrowness has previously been shown to be associated with slower travel speeds in many arboreal tetrapods, including tree frogs (Herrel et al, 2013), anoles (Losos and Sinervo, 1989; Losos and Irschick, 1996; Mattingly and Jayne, 2004;Hsieh, 2016), fence lizards (Sinervo and Losos, 1991), marsupial gliders (Karantanis et al, 2015), opossums (Lammers and Biknevicius, 2004;Shapiro et al, 2014), mice (Hyams et al, 2012), squirrels (Schmidt, 2011) and strepsirrhine primates (Stevens, 2007). Other gait adjustments were subtler, often displaying a complex interaction with speed.…”
Section: Influence Of Support Diameter On Gait Kinematicsmentioning
confidence: 99%
“…Though narrow supports and compliant substrates impose different mechanical constraints, both perturbations require precise control over CoM movements and force production if stability is to be maintained. Indeed, previous research has shown that when moving on precarious substrates, a variety of animals -including lizards (Hsieh, 2016), marsupials Young, 2010, 2012;Shapiro et al, 2014), rodents (Schmidt and Fischer, 2010;Schmidt, 2011), carnivores (Lemelin and Cartmill, 2010), quadrupedal primates (Schmitt, 1999;Schmitt et al, 2006;Wallace and Demes, 2008;Young, 2009) and humans (McMahon and Greene, 1979;Ferris et al, 1998;MacLellan and Patla, 2006) -tend to use a set of common strategies to increase stability. Such strategies include limiting the use of whole-body aerial phases, increasing substrate contact duration, more evenly distributing footfalls across a stride, reducing CoM height, mitigating fluctuations in CoM position and reducing the peak magnitude of vertical forces.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have examined locomotor kinetics following autotomy; however, a recent study of the leopard gecko, Eublepharis macularius, demonstrated that these animals adopted a more sprawled hindlimb posture following tail loss, along with reduced peak hindlimb vertical ground reaction forces (see Glossary), corrected for body size (Jagnandan et al, 2014). Similarly, recent work on green anoles, Anolis carolinensis, also demonstrated a more crouched hindlimb posture during perch running after tail autotomy (Hsieh, 2016). As more studies begin to measure ground reaction forces and detailed kinematics of running lizards before and after tail loss, we will be better positioned to develop predictive frameworks for understanding how autotomy influences locomotor behavior and performance.…”
Section: Ground Reaction Forcementioning
confidence: 99%
“…2), and so intact tails help to position the CoM closer to the hindlimbs where force is generated against the ground (Ballinger et al, 1979). Third, lizards adopt a more sprawled posture during running after autotomy (Hsieh, 2016;Jagnandan et al, 2014), suggesting that tails likely serve to improve balance and stability.…”
Section: Caudal Autotomy Often Impairs Runningmentioning
confidence: 99%
See 1 more Smart Citation